Roman Senchin: The poetics of Tuvan text - Shafranskaya, Eleonora F.; Garipova, Gulchira T.; Tokareva, Nadezhda A. (The New Research of Tuva, 2023)
The article examines the controversial issues of identifying the local text as a research category. The authors make an attempt to describe the Tuvan local text using the case of prosaic works by the contemporary writer Roman Senchin. The features of the Tuvan text are correlated with modern theories of local texts and the category of metatext. The formal and substantive aspects of the Tuvan text are outlined. In the course of the analysis of the author’s model of the Tuvan text — as a sign of Senchin’s metaconsciousness — we have determined the principles of textual representation of the levels of the artistic and existential matrix of genius loci compared with the metaimage of the paradise lost. It is noted that the matrix of the Tuvan text includes the image of the “hero of the way” who perceives the space of the “alien Tuva” as a discovered “own world”. The analytics of the article is fit in with the system of interdisciplinary paradigmatic connections of aesthetics, historiosophy, ethnography and mythology. It is concluded that understanding of the foreign ethnic and cultural component of Russian literature about Tuva as a historical and cultural phenomenon makes it possible to find manifestations of the Tuvan text in completely diverse authorial artistic systems.